SERUM OSTEOPONTIN LEVEL IS ASSOCIATED WITH PRESENCE OF ATRIAL FIBRILLATION IN CALCIFIC AORTIC VALVE STENOSIS - T A Tipteva; O S Chumakova; N E Reznichenko; V I Safaryan; T N Baklanova; N M Voloshina; D A Zateyshchikov (Клиническая практика, 2017)
Identification of risk factors associated with presence of atrial fibrillation (AF) in patients with aortic valve stenosis (AS) remains to be unraveled.The aim of the study was to investigate relationship between profibrotic biomarkers and presence of AF in AS patientsMethods. 191 patients (29,8% male, 77,7±0,59 years) with AS (defined as aortic valve area (AVA) ≤ 2,0 sm2) were enrolled in the study. Clinical, echocardiographic and biochemical variables, including serum TGFβ1 and osteopontin levels were compared between 2 groups of patients: with and without AF. Results. 83(36,5%) of AS patients had AF. In logistic regression models independent associations between AVA index (p=0,040), left atrial volume (p=0,021), OPN (р=0,009) and presence of AF were found. Patients with serum OPN level 10,05 ng/ml had twice more higher AF incidence comparedto patients with serum OPN level ≤ 10,05 ng/ml (53,8% and 29,2%, respectively, p=0,020).Conclusion. Serum OPN level was independently associated with presence of AF in AS patients, thus we speculate on it’s predominant profibrotic role in the left atrium.